Auto-reconstrução de um feixe bessel parcialmente coerente - Alves, Cleberson Rodrigues (2014)
In this work, we generate partially coherent zero order Bessel and Gaussian beams. We study their behavior along the propagation in free space after part of its transverse profile be obstructed by an opaque obstacle. We show that it is possible to retrieve the profile of the beam from the speckle pattern, using the autocorrelation. We introduce an effect that we call self-reconfiguration, which mimics the effect of self-reconstruction, but this case is not necessary to recover the pattern that existed before the obstruction. We show that the property of self-reconfiguration of a partially coherent beam is more robust that the property of self-reconstruction of a coherent beam. We observed that the effect of self-reconfiguration occurs even for beams which are non-coherently reconstructive, as is the case of the Gaussian beam. We found that the obstacle acts as a filter and that this effect in the autocorrelation depends on the relative area between blocked and unblocked speckles. We present numerical and experimental results, and arguments to explain the observations. The results may be useful for optical microscopy designed to look more deeply into scattering tissues and also for imaging through turbulent atmosphere.